1998
DOI: 10.1164/ajrccm.157.1.96-11086
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Exposure to Crocidolite and Mesothelioma

Abstract: This study aimed to estimate exposure-response relationships for mesothelioma and environmental exposure to crocidolite. All 4,659 former residents of Wittenoom, Western Australia (WA) who lived there between 1943 and 1993 for at least 1 mo and were not directly employed in the crocidolite industry, were followed-up through the WA death, cancer and mesothelioma registries, electoral rolls, and telephone books. In 1992, all subjects who should be traced were sent a questionnaire. Exposure levels were estimated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
119
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(132 citation statements)
references
References 14 publications
11
119
0
2
Order By: Relevance
“…11,13 These sources and the percent of people they identified included: state primary school records (22%), admission and out-patient records from the Wittenoom hospital and General Practitioner (20%), the State Electoral Roll for the Pilbara district (12%) questionnaires sent to ABA workers (14%), participants of a cancer prevention program and associated publicity (18%) and Wittenoom birth records (4%). Other sources included records from the Catholic Church, Wittenoom burial records, employment lists from the school, hotel, police, hospital and banks and information from the Asbestos Diseases Society of WA (10%).…”
Section: Wittenoom Workers' and Residents' Cohortsmentioning
confidence: 99%
See 2 more Smart Citations
“…11,13 These sources and the percent of people they identified included: state primary school records (22%), admission and out-patient records from the Wittenoom hospital and General Practitioner (20%), the State Electoral Roll for the Pilbara district (12%) questionnaires sent to ABA workers (14%), participants of a cancer prevention program and associated publicity (18%) and Wittenoom birth records (4%). Other sources included records from the Catholic Church, Wittenoom burial records, employment lists from the school, hotel, police, hospital and banks and information from the Asbestos Diseases Society of WA (10%).…”
Section: Wittenoom Workers' and Residents' Cohortsmentioning
confidence: 99%
“…14 Therefore follow up status at the end of 1993 was; 2,173 (47%) returned a questionnaire, 641 (14%) were participating in the cancer prevention program, 51 (1%) had permanently departed Australia, 460 (10%) were dead, 785 (17%) had not returned a questionnaire and 549 (11%) were not traced since leaving Wittenoom. 13 Where the person remained untraced, did not return a questionnaire or was dead: if they were related to an ABA worker, then dates and place of residence were assumed identical to that of the worker. For those unrelated to an ABA worker, dates of residence were assumed the same as other family members provided that at least one family member had known exposure.…”
Section: Wittenoom Workers' and Residents' Cohortsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, cases in Wittenoom were exposed to a combination of environmental, occupational and domestic exposure to asbestos and it was not possible to separate the effects of these different routes of exposure on the occurrence of MM (Reid et al, 2007;Reid et al, 2008a, b). An earlier study has shown that residents who had lived at least 5 years in the area and were not directly employed in the crocidolite industry had in increased relative risk of 6.7, which was attributed primarily to environmental exposure to asbestos (Hansen et al, 1998). Hence, it remains a question how sources of asbestos pollution in the general environment will influence exposure patterns among citizens living in that area and how well geographic exposure models are able to estimate the magnitude of asbestos exposure at an individual level.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 La primera descripción histológica de éste fue realizada por E. Wagner en 1870, y no fue sino hasta 1960 cuando J.C. Wagner y colaboradores establecieron una vinculación entre el mesotelioma maligno y la exposición a asbestos; así, describieron una enfermedad con un largo periodo de latencia, que afectaba fundamentalmente a mineros y trabajadores de molinos expuestos a crocidolita. [3][4][5] La incidencia del MM en el ámbito mundial es variable. En Estados Unidos de América (EUA) se han notificado 2 200 nuevos casos por año, con un incremento aproximado de 50% en la última década.…”
Section: Introductionunclassified